Analisis Kuat Tekan Beton Menggunakan Material Lokal Kalimantan Timur Dengan Penambahan Polyethylene Terephthalate - Safitri, Reza Ayu; Indriani, Andi Marini; Utomo , Gunaedy (Syntax Literate, 2025)
Plastic waste is a waste that is very difficult to decompose, this often causes environmental pollution. The plastic waste has a light weight and is not easy to deform. There are many types of plastic from polyethylene, One of which is PET (Polyethylene Terephthalate). In this study, a type of PET (Polytethylene Terephthalate) plastic with a width of 3mm and a length of 5mm with a test piece consisting of 80 cylinders, the test was carried out using an experimental method with compressive strength at the age of 7, 14, 21 and 28 days. The concrete mix design used the SK SNI 2384-2000 method and the planned concrete quality was 14.53MPa.The results of this study were on PET (Polytethylene Terephthalate) mixed concrete with 60 samples with variations in the percentage of PET (Polytethylene Terephthalate) of 0.7%, 0.85% and 1.0%. The highest compressive strength was recorded at a PET percentage of 0.7% at 28 days with a value of 16.05 MPa and the lowest compressive strength at a PET percentage of 1.0% at 28 days with a value of 11.67 MPa. The compressive strength decreases with the increase in plastic variety because the shape of the smooth surface of the plastic stone is not able to bind cement, the lightness of the plastic affects the weight of the concrete which continues to decrease as the amount of plastic inside and the aggregate of Petangs stone. Based on the results, the addition of PET to the compressive strength of concrete does not have a good effect.